Tropical forest conversion and its impact on indigenous communities Mapping forest loss and shrinking gathering grounds in the Western Ghats, India. (March 2021) - Vijayan, Dhanya; Kaechele, Harald; Girindran, Renoy; Chattopadhyay, Srikumar; Lukas, Martin C.; Arshad, Muhammad
Highlights: Forest plantations are major driver of tropical natural forest conversion. Natural forest loss threatens indigenous communities' livelihoods. Conserving forests is key to protect socio-economic and cultural traits of tribes. Operational areas of hunter-gatherers must be mapped and protected. Indian official forest system must disaggregate plantations from natural forests. Abstract: Conversions of natural forests to forest plantations threaten ecosystems and forest-dependent indigenous populations in many parts of the world. It is crucial to understand the scale and nature of such forest conversions and how they affect forest-dependent communities as a basis for prudent forest management and protection of indigenous livelihoods. This study analyses natural forest conversions and their impacts on tribal communities in the southern Western Ghats, a globally significant biodiversity hotspot. It focuses on two tribal settlements in protected forests within the catchment of the Achankovil River. The study involves time series analysis of forest cover change, based on a historical map and satellite images, field mapping of changes in the tribal communities' areas of operation, household surveys, and focus group discussions. The analysis shows that the area of protected forest decreased by 53 % from 1978 to 2015. As a result, the size of the tribal communities' gathering areas considerably shrunk, resulting in a decline in their collection of non-timber forest products and increased dependency on forest plantations labour for their livelihood. This is especially critical as the tribal communities still prefer to depend on natural forests for their sustenance. Preservation of natural forests is hence crucial not only for biodiversity conservation, but also to protect socio-economic and cultural traits of tribal populations.